Pemetaan Vegetasi Hutan Mangrove Menggunakan Metode Normalized Difference Vegetation Index (NDVI) di Desa Arakan, Minahasa Selatan, Sulawesi Utara - Philiani, Intan; Saputra, Livinia; Harvianto, Loecky; Muzaki, Anggi Afif (Surya Octagon Interdisciplinary Journal of Science and Technology, 2016)
Tatapaan District in North Minahasa has  mangrove forest covering an area of 8.736.00 m2. One of the village in Tatapaan District is Arakan. This study aim for mapping mangrove density in Arakan village and determine the best result of Normalized Difference Vegetation Index (NDVI) from band combination used. NDVI method calculate the amount of vegetation greeness value derived from digital signal processing of brightness value data of multiple channels satellite sensor data from satellite images. NDVI measures the slope between the original value of the red band and infrared band in the sky with the value of each pixel in the image. Imagery used is Worldview2 satellite image recording on June 19th 2014. Based on the combination of bands used, the best result of band combination is the combination of Red and NIR 2 band with the value of the smallest error rate of deviation, ie 0.3. The density of the widest is âRapatâ class (824,566.01 m2), âSedangâ class (133,622.41 m2), âJarangâ class (12,004.92 m2), âSangat jarangâ class (10,494.23 m2), and the smallest is âSangat rapatâ class (24.45 m2).